Effects on performance, combustion and pollutants of water emulsified fuel in an aeroengine combustor. (15th February 2020) - De Giorgi, Maria Grazia; Fontanarosa, Donato; Ficarella, Antonio; Pescini, Elisa
Highlights: Water in Jet-A1 fuels under lean conditions were studied on a swirl combustor. Pollutant emission measurements and high-speed visualizations were performed. The POD of the OH* chemiluminescence images characterized the flame instability. NOx reduction, weak efficiency loss and stable flame observed at 2.5% water content. Water content higher than 5% strongly reduced the thermal efficiency. Abstract: The present work provides an experimental investigation of the use of water emulsified fuels to control the combustion performance and reduce nitrogen oxides emissions into a Jet-A1 fueled gas turbine combustor. Experiments have been carried out using a test rig equipped with a 300-kW liquid-fueled swirling burner. Several fuel-to-air ratios have been tested in combination with various water concentrations. Measurements of exhaust emissions have been performed. Furthermore, high-speed cameras in visible and ultraviolet spectral ranges, have been used. The snapshot Proper Orthogonal Decomposition of the flame images of both broadband emission and hydroxyl radical chemiluminescence has allowed to detect the most relevant flame structures, in combination with the modal frequency spectra. Results figured out that, the addition of water in the fuels led to lower combustion temperature and consequently to lower thermal nitrogen oxides than the case of neat fuel. On the other hand, the thermal efficiency significantly dropped in presence of high-water content (5% H2 O) and ultra-lean conditions, while it remained acceptable at 2.5% H2 O and fuel rich conditions. Furthermore, under the near-lean blowout condition, the flame becomes very unstable and flame oscillations take place in the axial direction. This combines with the increase in the relative energy of the first Proper Orthogonal Decomposition modes. Finally, the phase space analysis of modes 1–2 of the hydroxyl radical chemiluminescence emission defined a criterion for the detection of the establishment of the flame instability, which corresponds to phase angles ranging between -π/6 and π/6.